HALAL TOURISM POTENTIAL OF CEMARA INDAH BEACH IN DEVELOPING THE COMMUNITY BUSINESS SECTOR - Yulindawati, Yulindawati (EKOBIS SYARIAH, 2025)
The results of the research show that the tourism potential of Cemara Indah Beach which can support the development of the community's business sector is the location of the tourist attraction close to residential areas so that people can easily open their businesses, Cemara Indah Beach is close to the national road so it has the potential for small businesses from the community, the potential of the sea and a very beautiful beach, the natural beauty around Cemara Indah Beach that supports it, the availability of good facilities and infrastructure, providing tourist facilities for children and adults, the availability of various culinary foods for visitors and the existence of artificial park tourist attractions, sports fields and play areas children. The potential impact of Cemara Indah Beach tourism on the community business sector is the emergence of various types of community businesses such as opening kiosks selling snacks, traditional culinary businesses, the emergence of businesses providing tourist facilities, games rental businesses for visiting children and the existence of a managed culinary business sector. by BUMG Gampong Ujong Batee.